The Role of PAI Teachers in Learning Model Innovation in the Era of Society 5.0 Case Study - Novia Rizka Saptania; Mohammad Saat Ibnu Waqfin (SCHOOLAR: Social and Literature Study in Education, 2023)
s educators, teachers have an important role in the learning process. In realizing learning that can arouse students' enthusiasm, teachers should have creative, interesting learning models. Especially in the era of society 5.0 where the learning process must take advantage of technological sophistication, this requires teachers to have innovative, creative learning models so that students are active in class and can understand the material well. The purpose of this study was to find out the innovative learning models used by PAI teachers in the era of society 5.0. This research can also be used as a learning evaluation and reference in finding effective innovative learning models. The approach used to achieve the above objectives is by using a qualitative approach with a type of field study research. In collecting data the author uses the method of observation, interviews, and documentation. The results of the study show that: 1. The learning model innovation at MAN 3 Jombang is by making interesting learning media such as: PPT, e-books, and Quizizz. In addition, the application of a learning model in the form of CTL (Contextual Teaching Learning) can train students to think critically and creatively. 2. The strategy used is to design creative learning media so that students are interested during the learning process. 3. Obstacles experienced by PAI MAN 3 Jombang teachers, namely the lack of stability of the school's internet connection and the limited access of laptops by students living in Islamic boarding schools